Closed Reduction and Immobilization of Pediatric Fifth Metacarpal Neck Fractures. (May 2022) - Lee, Stella J.; Merrison, Hannah; Williams, Kathryn A.; Vuillermin, Carley B.; Bauer, Andrea S.
Background: There is no clear consensus for the criteria for closed treatment of metacarpal neck fractures. Our objective was to determine whether closed reduction of pediatric fifth metacarpal neck fractures results in a clinically meaningful improvement in radiographic angulation. Methods: We performed a retrospective cohort study of pediatric patients with fifth metacarpal neck fractures treated with closed reduction. Radiographs were examined for sagittal fracture angulation measured post-reduction, 2 to 14 days post-reduction, and 21 to 35 days post-reduction. We compared the angulation for open versus closed physes, initial fracture angulation greater than or less than 50°, and immobilization in extension versus intrinsic-plus position. Results: Fifty-four subjects were included with an average age of 14.8 years at the time of injury and a mean initial fracture angulation of 42.7°. The improvement in fracture angulation was 8.3° (90% confidence interval [CI], 5.9-10.7) on post-reduction radiographs, 8.5° (90% CI, 6.1-10.9) at 2 to 14 days post-reduction, and 4.3° (90% CI, 1.4-7.2) at 21 to 35 days post-reduction. Subgroup analysis showed that patients with injury angle greater than or equal to 50° had significantly higher mean reductions than those with injury angle less than 50°. In this group, angulation improved 15.6° (90% CI, 8.5-22.7) post-reduction, 15.1° (90% CI, 10.1-20.1) at 2 to 14 days post-reduction, and 16.5° (90% CI, 10.4-22.6) at 21 to 35 days post-reduction. Conclusions: Closed reduction of pediatric fifth metacarpal neck fractures with initial fracture angulation less than 50° may not meaningfully improve sagittal alignment. For fractures with initial angulation greater than or equal to 50°, closed reduction resulted in clinically important, statistically significant, and lasting improvements of 16.5°.